AhR modulates the IL‐22‐producing cell proliferation/recruitment in imiquimod‐induced psoriasis mouse model. Issue 6 (9th June 2016) - Cochez, Perrine M.; Michiels, Camille; Hendrickx, Emilie; Van Belle, Astrid B.; Lemaire, Muriel M.; Dauguet, Nicolas; Warnier, Guy; de Heusch, Magali; Togbe, Dieudonnée; Ryffel, Bernhard; Coulie, Pierre G.; Renauld, Jean‐Christophe; et al.
Abstract : In the imiquimod‐treated ears, we showed that AhR is required for IL‐22 production by Th17, but not by γδ T cells, CD4 − CD8 − TCRβ + T cells, and ILCs. By contrast, AhR has a role in the proliferation/recruitment of γδ T cells, ILC3, and CD4 − CD8 − TCRβ + T cells into the inflamed skin. Abstract : IL‐22 has a detrimental role in skin inflammatory processes, for example in psoriasis. As transcription factor, AhR controls the IL‐22 production by several cell types (i.e. Th17 cells). Here, we analyzed the role of Ahr in IL‐22 production by immune cells in the inflamed skin, using an imiquimod‐induced psoriasis mouse model. Our results indicate that IL‐22 is expressed in the ear of imiquimod‐treated Ahr −/− mice but less than in wild‐type mice. We then studied the role of AhR on three cell populations known to produce IL‐22 in the skin: γδ T cells, Th17 cells, and ILC3, and a novel IL‐22‐producing cell type identified in this setting: CD4 − CD8 − TCRβ + T cells. We showed that AhR is required for IL‐22 production by Th17, but not by the three other cell types, in the imiquimod‐treated ears. Moreover, AhR has a role in the recruitment of γδ T cells, ILC3, and CD4 − CD8 − TCRβ + T cells into the inflamed skin or in their local proliferation. Taken together, AhR has a direct role in IL‐22 production by Th17 cells in the mouse ear skin, but not by γδ T cells, CD4 − CD8 − TCRβ + T cells and ILCs.